INTERPRETASI LITOLOGI BERDASARKAN DATA LOG SINAR GAMMA, RAPAT MASSA, DAN TAHANAN JENIS PADA EKSPLORASI BATUBARA - I N D A , W
In coal exploration, the target to be achieved is its reserve's economic value.To estimate this reserve, the thickness datas of coal beddings is needed.Well logging is one of the geophysical methods which is relatively accurate in determination of the thickness and depth of a certain layer comparing to any other methods. The problem of this method is mainly in its technique of interpretation, because it is neccessary to have an experienced personnels of the method. The interpretation of log datas in this thesis is not detatched from the geologist's opinion , however the interpretation procedure can be simplified in the form of computer program, so as to decrease the interdependency on geologist.This program in Fortran-77 is too simple because it sorts the log deflection values which will then be defined in lithologic units.From the results of the mentioned lithologic analysis, drawing is done by the Rockware (Logger) program packet. According to the research results of the Directorate of Coal, four potential coal seams are found in the Muara Enim Formation at the south of Muara Tiga, these includes seam A (A-1 and A-2), thin Suban seam, seam B, and seam C (C-1 and C-2). Each of the mentioned coal layers appears in the log datas which indicates low gamma ray deflection (< 100 cps/in), very low density (1.2 to 1.3 gr/cm3 ), and high resistivity (> 110 Ohm-m).And then, the mentioned log deflection values are used as reference in the program and these four coal layers appeared in the program's output from the 8(eight) wells, that is from MTS-01 to MTS-08. Furthermore, the thickness of coal bedding have been fitted with the core drilling datas especially with MTS-05 and MTS-06 ; apparrently its error factor ranges from 1.31 % to 5.9 %, and the correlation among the mentioned stratigraphic sections of the two wells can be done based on the statistical tests. However, the whole correlation is done based on the thin Suban seam.